2000 Special Merit Award for Outstanding Achievement in Community Dentistry-International: - B. Alex White, DDS, DrPH (Blackwell Synergy, 2001)
Two years ago, the American Association of Public Health Dentistry instituted a new award to recognize the contributions of our international colleagues in improving the public‘s oral health. This year, the AAPHD is pleased to recognize Dr. John J. Clarkson by presenting him with the Special Merit Award for Outstanding Achievement in Community Dentistr y-Interna tional.